2013
DOI: 10.3109/15412555.2013.854322
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and Intratracheal Mesenchymal Stromal Cell Injection in a Mouse Model of Pulmonary Emphysema

Abstract: The aim of this study was to characterize the evolution of lung function and -structure in elastase-induced emphysema in adult mice and the effect of mesenchymal stromal cell (MSC) administration on these parameters. Adult mice were treated with intratracheal (4.8 units/100 g bodyweight) elastase to induce emphysema. MSCs were administered intratracheally or intravenously, before or after elastase injection. Lung function measurements, histological and morphometric analysis of lung tissue were performed at 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
2
28
1
Order By: Relevance
“…Initially this work sought to establish the optimal dose for human MSC therapy in this model. While studies have compared different rodent MSC sources30 and delivery routes3045 this is the first study to demonstrate a dose response. In line with hMSC dose selection based on hMSC/kg weight for human trials, a dose dependency study was performed based on animal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Initially this work sought to establish the optimal dose for human MSC therapy in this model. While studies have compared different rodent MSC sources30 and delivery routes3045 this is the first study to demonstrate a dose response. In line with hMSC dose selection based on hMSC/kg weight for human trials, a dose dependency study was performed based on animal weight.…”
Section: Discussionmentioning
confidence: 99%
“…The best route remains to be determined but one recent study suggested that IT administration of MSCs was more efficacious that IV using the neonatal rat hyperoxia model 53 . In contrast, IV MSC injection halted lung deterioration whereas IT MSCs had no effect on lung histology or dysfunction in an adult mouse model of elastase-induced emphysema 54 , pointing to potentially disease-specific and age-specific differential responses to the most optimal route for MSC delivery.…”
Section: Introductionmentioning
confidence: 93%
“…In asthma, however, mast cells, eosinophils and Th2 lymphocytes are involved in further aggravation of airway hyperresponsiveness and bronchoconstriction [117]. In rodent models of elastase-induced emphysema or cigarette-induced COPD, MSC infusion reduces lung destruction and aberrant inflammation [118, 119]. MSC-secreted epidermal growth factor (EGF) leads to induction of secretory leukocyte protease inhibitor (SLPI), an inhibitor which protects epithelial tissues from serine protease degradation [120, 121].…”
Section: State Of Msc Clinical Research In Specific Immune-/inflammatmentioning
confidence: 99%